Redistribution within the tax-benefit system in Austria - Michael Christl; Monika Köppl-Turyna; Hanno Lorenz; Dénes Kucsera (Agenda Austria, 2020)
The aim of this study is to analyze redistribution within the Austrian tax-benefit system. In this work we take a comprehensive view and include not only direct taxation and cash benefits, but also indirect taxes and in-kind transfers. We look at two kinds of redistribution: between the households belonging to different income groups, and between generations, taking the life-cycle perspective. Our analysis shows that indirect taxes, as known from the previous literature, have a regressive effect on the tax-benefit system. On the contrary, in-kind benefit seem to have a progressive effect. To analyse the impact of both, we extend our income concept by both, indirect taxes and in-kind benefits. If we look on the distributional impact, we find that the inequality-enhancing effect of indirect taxes is more than off-set by the inequality-reducing effect of in-kind benefits. The Gini coefficient increases form 0.24 to 0.26 due to indirect taxes, but when adding in-kind ben- efits, the Gini coefficient is reduced to 0.23. The overall effect of both, indirect taxes and in-kind benefits is progressive.
Keywords: I38; H24; D31; 330; tax-benefit model; EUROMOD; welfare state; Austria; in-kind benefits